Symptomatic, radiological and pathological involvement of the hypothalamus in neuromyelitis optica. Issue 6 (15th May 2009) - Viegas, S; Weir, A; Esiri, M; Kuker, W; Waters, P; Leite, M I; Vincent, A; Palace, J
Abstract : This study describes a young girl who presented with involuntary weight loss, spontaneous vomiting and behavioural change. Imaging confirmed hypothalamic and brainstem involvement. Routine investigations (including cerebrospinal fluid analysis and neuromyelitis optica IgG) were unhelpful. Biopsy of the hypothalamic lesion implicated an aggressive inflammatory aetiology. There was a response to conventional immunosuppression, while a further relapse responded to plasma exchange. She died 21 months after presentation. Postmortem examination was highly suggestive of neuromyelitis optica, which was subsequently confirmed following the identification of aquaporin 4 antibodies.